Reproductive Health Knowledge and Premarital Sexual Behavior in Srumbung District, Magelang Regency - Pertiwi, Nur Fitri Ayu; Abida, Liza Laela; Lestari, Puspita Hanggit (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Premarital sexual behavior often occurs during adolescence. Adolescence is a transition period from childhood to adulthood. This period allows deviations to occur. Uncontrolled premarital sexual behavior can result in unwanted pregnancies which will damage the future of teenagers and their environment. This deviation is closely related to teenagers' lack of knowledge regarding reproductive health. Reproductive health knowledge is not only about changes during puberty, but also about the limits of relationships with the opposite sex. The aim of the research was to determine the relationship between reproductive health knowledge and premarital sexual behavior among teenagers. The research method uses a cross sectional design with a questionnaire measuring instrument that has been tested for validity. Using the Pearson test with 95 respondents. Keywords: reproductive health knowledge, behavior, premarital sex